Gaya Hidup dan Pola Makan dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Piyungan DIY 2023: Gaya Hidup, Pola Makan, Hipertensi - Hodiri Adi Putra; Parmadi Sigit Purnomo; Silvia Violita Shelvany (Jurnal Penelitian Multidisiplin, 2023)
Based on data from the Bantul Health Office, the highest cases of hypertension were in the working area of the Piyungan Health Center with 1,383 new cases and 5,215 confirmed old cases with a total of 6,634 hypertension cases. Based on a preliminary study at the Piyungan Health Center, interviews were conducted with the Head of the Non-communicable Diseases Coordinator and the Head of the Nutrition Coordinator for the Piyungan Health Center, obtained data that the total number of new hypertension client visits in September was 36 people from all work areas of the Piyungan Health Center, from these data there were many people who experienced the incidence of hypertension with the most influence on the incidence of hypertension caused by lifestyle and diet. The purpose of this study was to determine the relationship between lifestyle and eating patterns with the incidence of hypertension in the working area of the Piyungan Health Center, Special Region of Yogyakarta. Total population of 36 people. The sampling technique used the total sampling technique. The samples in this study were 36 cases and 36 controls with a total of 72 respondents. The research instrument used a questionnaire and the results were analyzed using the Chi Square test.